p53 represses c-Myc through induction of the tumor suppressor miR-145 - Sachdeva, Mohit (National Academy of Sciences, 2009)
The tumor suppressor p53 negatively regulates a number of genes, including the proto-oncogene c-Myc, in addition to activating many other genes. One mechanism of the p53-mediated c-Myc repression may involve transcriptional regulation. However, it is not clear whether microRNAs (miRNAs) play a role in the p53-mediated posttranscriptional regulation of c-Myc. In this study, we show that a putative tumor suppressor, miR-145, is expressed through the phosphoinositide-3 kinase (PI-3K)/Akt and p53 pathways. Importantly, p53 transcriptionally induces the expression of miR-145 by interacting with a potential p53 response element (p53RE) in the miR-145 promoter. We further show that c-Myc is a direct target for miR-145. Although miR-145 silences the expression of c-Myc, anti-miR-145 enhances its expression. This specific silencing of c-Myc by miR-145 accounts at least in part for the miR-145-mediated inhibition of tumor cell growth both in vitro and in vivo. Finally, the blockade of miR-145 by anti-miR-145 is able to reverse the p53-mediated c-Myc repression. Together, these results define the role of miR-145 in the posttranscriptional regulation of c-Myc by p53 and suggest that, as a new member of the p53 regulatory network, miR-145 provides a direct link between p53 and c-Myc in this gene regulatory network.